Magnitude and temporal trends of leprosy relapse in the state of Ceará, Brazil in the period 2001-2018 - Reagan Nzundu Boigny; Caroline Mary Gurgel Dias Florêncio; Kellyn Kessiene de Sousa Cavalcante; Jarier de Oliveira Moreno; Pedro José de Almeida; Jardel Gonçalves de Sousa Almondes; Paula Sacha Frota Nogueira; Carlos Henrique Alencar (Revista da Sociedade Brasileira de Medicina Tropical, 2021)
Abstract INTRODUCTION: This study analyzed the magnitude and temporal trends of leprosy relapse in Ceará in 2001-2018. METHODS: Descriptive cross-sectional and ecological-time trend studies were performed. RESULTS: We diagnosed 1,777 leprosy relapse cases. Higher prevalence of relapse was observed in men, illiterates, mixed race, multibacillary leprosy, lepromatous leprosy, and persons with visible disabilities. The proportion of relapse increased throughout the study period. CONCLUSIONS: Leprosy relapse is prevalent in certain groups.